Cardiac magnetic resonance follow-up of COVID-19 vaccine associated acute myocarditis - Kravchenko, Dmitrij; Isaak, Alexander; Mesropyan, Narine; Bischoff, Leon M.; Pieper, Claus C.; Attenberger, Ulrike; Kuetting, Daniel; Zimmer, Sebastian; Hart, Christopher; Luetkens, Julian A. (Frontiers in Cardiovascular Medicine, 2022)
Background Mass COVID-19 vaccination campaigns have helped impede the COVID-19 pandemic. In rare cases, some vaccines have led to vaccine associated myocarditis in a specific subset of the population, usually young males. Cardiac magnetic resonance (CMR) can reliably diagnose vaccine associated myocarditis, but follow-up data of CMR proven acute myocarditis is scarce. Methods Nine patients with acute vaccine associated myocarditis underwent baseline and follow-up CMRI examinations and were compared to baseline parameters at initial presentation and to a group of 20 healthy controls. CMR protocol included functional assessment, T1 and T2 mapping, T2 signal intensity ratio, strain feature tracking, and late gadolinium enhancement (LGE). Results Myocarditis patients (n=9, aged 24±6 years, 8 males) underwent CMR follow‐up after an average of 5.8±4.3 months. All patients showed a complete resolution of visual myocardial edema while also demonstrating a reduction in overall LGE extent from baseline to follow-up (4.2±2.1% vs. 0.9±0.8%, p<.001), although visual LGE was still noted in all patients. Left ventricular ejection fraction was normal at baseline and at follow-up (58±6 vs. 62±4%, p=.10) as well as compared to a healthy control group (60±4%, p=.24). T1 (1024±77 ms vs. 971±34 ms, p=.05) and T2 relaxations times (57±6 ms vs. 51±3 ms, p=.03) normalized at follow-up. Most patients reported a resolution of clinical symptoms, while two (22%) reported new onset of exertional dyspnea. Conclusion Patients with COVID-19 vaccine associated acute myocarditis showed a complete, uncomplicated resolution of myocardial inflammation on follow-up CMR, which was associated with a near complete resolution of symptoms. Minor, residual myocardial scarring was present on follow-up LGE imaging. The long-term implications of the remaining myocardial scar-tissue after vaccine associated myocarditis remain unknown warranting further studies.